Descemet Stripping Only Technique for Corneal Endothelial Damage in Mice. Issue 4 (22nd April 2023) - Nakagawa, Hayate; Alemi, Hamid; Wang, Shudan; Kahale, Francesca; Blanco, Tomas; Liu, Catherine; Yin, Jia; Dohlman, Thomas H.; Dana, Reza
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Purpose: Descemet stripping only is an emerging surgical technique used to remove central Descemet membrane and corneal endothelial cells in patients with corneal endothelial disease. Here, we describe a murine model of this procedure to help facilitate basic science investigation and evaluation of postoperative outcomes using this surgical technique. Methods: Slitlamp biomicroscopy, central corneal thickness assessment (by optical coherence tomography), and immunohistochemistry were used to assess the model through 7 weeks of follow-up. Results: Complete removal of the endothelium and Descemet membrane was confirmed by slitlamp biomicroscopy and by histology. Central corneal thickness peaked at day 1 postinjury and then declined over the course of 2 weeks to a stable level of persistent edema. Seven weeks postinjury, immunohistochemical staining for ZO-1 showed the area of Descemet stripping was fully covered by enlarged and dysmorphic corneal endothelial cell. No significant ocular complications were appreciated through the end of the follow-up. Conclusions: We demonstrate the feasibility of and provide detailed instructions for a murine model of Descemet stripping only. This model provides a potential in vivo platform to investigate the mechanisms and biology of this emerging surgical procedure.